Socio-Economic Condition of Communities in Resolving Conflicts in the Bukit Tangkiling Conservation Area - Saptawartono Saptawartono; Kumpiady Widen; Hendrik Segah; Yanarita Yanarita (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The Bukit Tangkiling Conservation Area has great potential for natural resources, including clean water, honey bees, recreation services, and religious services. There is also potential for split stone, which had been mined by the people from the rock hills in the area. The potential utilization of these natural resources trigger conflicts between interests to maintain the function and existence of conservation areas with the interests of using split stone for the community in order to meet the development needs of the city of Palangka Raya and its surrounding regions, at the cost of damaging the existing area. As an input in managing the conservation area Bukit Tangkiling is well implemented, research is needed on the social and economic conditions of the community’s surrounding the area. The research used survey methods and respondents are determined by purposive sampling and simple random sampling, and data analysis was both qualitative and quantitative. The communities around the Bukit Tangkiling conservation area are dominated by productive age (18-56 years), Banturung Village 59.00% and Tangkiling Village 54.97%. The level of education is relatively low, Banturung Village 72.96% and Tangkiling Village 73.29%. Having low education, most of the people have difficulty in finding decent work. Aside from that, most people do not understand the function of the forest or the function of the conservation area and tend to be apathetic about the existence of the Bukit Tangkiling conservation area that must be preserved. For some of these poorly educated people, the work of mining rocks is the best alternative to meeting the economic needs of the household. Income obtained from mining rock ranges from 2-4 million IDR per month.